Settlement pattern corruption problem in rural areas and alternative approaches: experiences in Beysehir - Emen, Turkey - Levend, Sinan; Meşhur, Mehmet Çağlar; Serdaroğlu Sağ, Neslihan (International Planning History Society Proceedings, 2016)
Rural areas are under different types of pressure due to their geographical locations in the country, distance to the urban areas and their natural and cultural features. Managing of this pressure is important in terms of conservation of settlement character and sustainability of spatial features of the rural areas. In Turkey, different approaches and models have been developed for the rural areas since the first years of republic. These policies, which were produced with names such as community development, central village, village city, agriculture city, have contributed to social and economic development of rural areas. However, spatial corruption of rural areas could not be prevented although economic development was created with difference policies and strategies. In this context, the main objective of this study is to examine factors causing spatial corruption of rural areas. In light of the findings obtained, approaches on conservation and sustainability of rural areas were discussed. In order to discuss and develop solutions for this problem, a protocol was signed between the Ministry of Environment and Urbanization, Karadeniz Technical University and Selcuk University in 2010. The project named " Rural Planning Focusing on Conservation: A Proposal Model" targeted to be developed with the cooperation of these institutions was supported by Turkey Scientific and Technical Research Organization and this project was completed in 2015. Within the project, field researches have been made in two different areas of Turkey by two Universities. In light of the findings, character of the settlements were determined and these findings have been entry in planning works in two example settlements selected. Findings obtained with the field research made by the project team have been base for the structural plan study in Emen, which is in Beysehir Lake's basin, one of the most important fresh water basins in Turkey. The reason why Emen selected in the project is that it has important values in terms of natural and cultural landscaping. The most important subject that should be emphasized within the findings obtained as result of the study is that the rural settlements are different than urban areas in terms of their road width and tissues, parcel sizes, floor area ratio and building heights. Another result is that "rural-specific" approaches, which would direct spatial development and construction in rural areas, have not been developed in Turkey. Supervision of spatial development and construction in rural areas with regulations and laws on development of urban areas has caused corruption in settlement character/fabric of the rural areas. Thus, "rural-specific" approaches should be developed for conserving settlement fabric/pattern in rural areas for increasing resilience against construction pressure.